APRENDIZAJE SIGNIFICATIVO: DE LA TRANSFORMACIÓN EN LAS CONCEPCIONES ACERCA DE LAS FORMAS DE INTERACCIÓN - Garita Sánchez, Gustavo (2001)
The article presents some reflections about the implications inherent to significative learning processes. In the beginning it deals with the value that specific forms of interaction, shaped in each group´s learning dynamics, represent for the individual reflection and elaboration regarding the object of knowledge. At the same time, it establishes the importance to modify mechanical views regarding such interactions, in such way that a change in the conceptions regarding a process of conscientiousness could translate in behaviors with a sense of direction towards the elaboration of significants.